Some aspects of common law shared ownership of housing ("Journal "U". Economy. Management. Finance.", 2023)
This article examines some aspects of the right of shared ownership of housing, which is one of the forms of ownership of residential premises. The author explores the basic principles and legal aspects of this form of ownership, as well as identifies the features and problems associated with its application. The article highlights issues related to the rights and obligations of owners within the framework of shared ownership of housing. It analyzes the legal mechanisms governing the management and distribution of common rights and obligations between owners, as well as the principles of decision-making and conflict resolution within the co-ownership community. Based on the analysis of judicial practice and regulatory legal acts, the author draws conclusions about trends and problems arising in the field of shared ownership of housing, and offers some recommendations for improving legislation and practice of applying this form of ownership.
Keywords: shared ownership; residential premises; restrictions; owners; disposal